2021
DOI: 10.3390/su131810006
|View full text |Cite
|
Sign up to set email alerts
|

Less Food Wasted? Changes to New Zealanders’ Household Food Waste and Related Behaviours Due to the 2020 COVID-19 Lockdown

Abstract: Food waste is a crisis of our time, yet it remains a data gap in Aotearoa New Zealand’s (NZ’s) environmental reporting. This research contributes to threshold values on NZ’s food waste and seeks to understand the impact of the 2020 COVID-19 lockdown on household food waste in NZ. The data presented here form part of the ‘Covid Kai Survey’, an online questionnaire that assessed cooking and food planning behaviours during the 2020 lockdown and retrospectively before lockdown. Of the 3028 respondents, 62.5% threw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 28 publications
(44 reference statements)
2
20
0
Order By: Relevance
“…Previous research from Spain has reported that reduced food waste during the COVID-19 lockdown was related to reduced shopping frequency, improved food management and preparing more creative recipes with leftovers ( 62 ). Likewise, changes in household food management and reduced food waste has been reported in Italy ( 73 , 74 ) and New Zealand ( 75 ). Further, participants in the present study discussed food waste in relation to concerns over food access and availability, corresponding with a Tunisian study ( 76 ) which suggested that reduction in food waste during COVID-19 lockdown was likely to be driven by socioeconomic factors rather than environmental concern.…”
Section: Discussionmentioning
confidence: 94%
“…Previous research from Spain has reported that reduced food waste during the COVID-19 lockdown was related to reduced shopping frequency, improved food management and preparing more creative recipes with leftovers ( 62 ). Likewise, changes in household food management and reduced food waste has been reported in Italy ( 73 , 74 ) and New Zealand ( 75 ). Further, participants in the present study discussed food waste in relation to concerns over food access and availability, corresponding with a Tunisian study ( 76 ) which suggested that reduction in food waste during COVID-19 lockdown was likely to be driven by socioeconomic factors rather than environmental concern.…”
Section: Discussionmentioning
confidence: 94%
“…A possible explanation for why meal kit use was lowest in single-person households may be that most ingredient boxes are designed for at least two people. Purchasing a meal kit just for one person may not be financially viable and/or result in greater food waste ( 26 ). Meal kits would benefit from including information about how to modify recipes to reduce energy intake or suggest alterations in portion size for those with lower energy requirements or one person ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The original COVID Kai Survey contained 100 variables, including questions regarding perceived cooking ability, a food frequency questionnaire, and sources of nutritional advice, amongst other topics. Many of these variables have been discussed elsewhere ( 24 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, another study conducted in Brazil (Cequea et al, 2021 ), seeking to compare Brazilian and Peruvian changes in food behaviour during the pandemic, underlined the employment of food management practices in connection with concerns about food practices and the price of food. In contrast, a study conducted in New Zealand (Sharp et al, 2021 ) showed that people who struggled to acquire money for food were more likely to waste food during the lockdown compared to the pre-pandemic era. This finding contradicts studies noting the relevance of socio-economic and financial factors in reducing consumer food waste (Jribi et al, 2020 ).…”
Section: Systematic Literature Reviewmentioning
confidence: 95%
“… Economic factors : Economic factors can be defined as external factors that relate to the economic context in which consumers make purchases. Primarily, the studies investigated the economic factor of food price changes, highlighting the influence of these changes on consumer choice (Babbitt et al, 2021 ; Cequea et al, 2021 ; Qian et al, 2020 ; Roe et al, 2020 ; Schmitt et al, 2021 ; Sharp et al, 2021 ). Behavioural factors : In the reviewed papers, behavioural factors tended to relate to food purchasing, preparation, and management.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%